Distribution and Abundance of Necrophagous Flies (Diptera: Calliphoridae and Sarcophagidae) in Maranhão, Northeastern Brazil. Issue 1 (13th June 2015) - Pereira de Sousa, José Roberto; Carvalho-Filho, Fernando da Silva; Esposito, Maria Cristina
Abstract : This study aimed at surveying the local calliphorid and sarcophagid species in Maranhão State (Brazil) to determine their distribution and abundance, as well as the distribution of exotic Chrysomya species. In total, 18, 128 calliphorid specimens were collected, distributed in 7 genera and 14 species. The species Hemilucilia semidiaphana (Rondani, 1850) and Paralucilia paraensis (Mello, 1969) were new state records. Chrysomya albiceps (Wiedemann, 1819) and Cochliomyia macellaria (F., 1775) were the most abundant species, and the exotic species of Chrysomya together contributed more than 50% of total blow fly abundance. The abundance distribution of the calliphorid community conformed to a log series model, characterized by a steep curve that reflects an assemblage with a high degree of dominance. For the Sarcophagidae, a total of 14, 810 specimens were collected and distributed in 15 genera, 11 subgenera, and 52 species. Tricharaea ( Sarcophagula ) occidua (F., 1794) and Peckia ( Sarcodexia ) lambens (Wiedemann, 1830) were the most abundant species. The abundance distribution of the species followed a log normal model, with a gentler slope, consistent with a more uniform community. The cumulative species curve for the sarcophagids did not reach the asymptote. Forty-three sarcophagid species were new state records and 22 were new records for the Brazilian northeast, which emphasizes the need for a continued survey in this region.